Breeding Dispersal by Birds in a Dynamic Urban Ecosystem - Marzluff, John M.; DeLap, Jack H.; Oleyar, M. David; Whittaker, Kara A.; Gardner, Beth (PLOS ONE, 2016)
Changes in land cover during urbanization profoundly affect the diversity of bird communities, but the demographic mechanisms affecting diversity are poorly known. We advance such understanding by documenting how urbanization influences breeding dispersal—the annual movement of territorial adults—of six songbird species in the Seattle, WA, USA metropolitan area. We color-banded adults and mapped the centers of their annual breeding activities from 2000–2010 to obtain 504 consecutive movements by 337 adults. By comparing movements, annual reproduction, and mate fidelity among 10 developed, 5 reserved, and 11 changing (areas cleared and developed during our study) landscapes, we determined that adaptive breeding dispersal of sensitive forest species (Swainson’s Thrush and Pacific wren), which involves shifting territory and mate after reproductive failure, was constrained by development. In changing lands, sensitive forest specialists dispersed from active development to nearby forested areas, but in so doing suffered low annual reproduction. Species tolerant of suburban lands (song sparrow, spotted towhee, dark-eyed junco, and Bewick’s wren) dispersed adaptively in changing landscapes. Site fidelity ranged from 0% (Pacific wren in changing landscape) to 83% (Bewick’s wren in forest reserve). Mate fidelity ranged from 25% (dark-eyed junco) to 100% (Bewick’s wren). Variation in fidelity to mate and territory was consistent with theories positing an influence of territory quality, asynchronous return from migration, prior productivity, and reproductive benefits of retaining a familiar territory. Costly breeding dispersal, as well as reduced reproductive success and lowered survival cause some birds to decline in the face of urbanization. In contrast, the ability of species that utilize edges and early successional habitats to breed successfully, disperse to improve reproductive success after failure, and survive throughout the urban ecosystem enables them to maintain or increase population size.